Ni Ketut Arini: A Bali Performing Arts Maestro - Gusti Ayu Ketut Suandewi; Sulistyani Sulistyani; Anak Agung Ketut Oka Adnyana; Tjokorda Istri Putra Padmini (RIRAI Publisher, 2023)
Ni Ketut Arini, who is popularly called Mrs. Arini, is a maestro of Balinese performing arts. This article will discuss the maestro's progress, who is known as a multi-talented artist with a long history of preserving this regional performing arts. In Bali, there are many performing arts artists. However, of the many artists referred to, it seems that not many have track records throughout Mrs. Arini's career. The questions: how is Mrs. Arini's progress in preserving traditional Balinese performing arts?. This research was conducted using the life history method. The data sources for this research were Mrs. Ni Ketut Arini herself, her colleagues, her students at Sanggar Warini and related communities who were selected based on purposive sampling and snowball. All data collected through observation, interviews, and literature studies were analyzed using Bourdieu's theory of aesthetics and social action theory. The results of the study show that Ni Ketut Arini is an artist who graduated from the Indonesian Art College (STSI) in Denpasar, and most of her life has been dedicated to the preservation of Balinese performing arts. Since the age of 14, Ni Ketut Arini has mastered Balinese traditional dance. Her skill in dancing traditional Balinese dance has made Ibu Arini have many students and become a role model for artists in Bali. Mrs. Arini is known for consistently preserving traditional Balinese dance. Through the Warini Studio that she cares for, Mrs. Arini continues to strive to care for, maintain, and develop this Balinese performing art to attract Balinese cultural tourism.